Effects of Void Fractions on Vibration Behaviour of Pipe Conveying Fluids - MOHD SAIFUDDIN, MUHAMMAD SYAMIM (IRC, 2021)
Topology in a piping system is an important aspect to be considered for designing a safety piping system.